Structural basis of cholesterol binding by a novel clade of dendritic cell modulators from ticks. Issue 1 (December 2017) - Roversi, Pietro; Johnson, Steven; Preston, Stephen; Nunn, Miles; Paesen, Guido; Austyn, Jonathan; Nuttall, Patricia; Lea, Susan
Abstract Two crystal structures of Japanin, an 18 kDa immune-modulatory lipocalin from the Brown Ear Tick (Rhipicephalus appendiculatus ), have been determined at 2.2 and 2.4 Å resolution. In both crystal forms the protein is in complex with cholesterol, which sits in a closed pocket at the centre of the lipocalin barrel. Both crystal forms are dimers, which are also observed in solution. Molecular modelling suggests that previously-described members of a tick protein family bearing high sequence homology to Japanin are also likely to bind cholesterol or cholesterol derivatives.